Super Planckian Thermal Radiation Emitted From a Nano-Filament of Photonic Crystal: A Direct Imaging Study - Mei-Li Hsieh; Shawn-Yu Lin; Sajeev John; James A. Bur; Xuanjie Wang; Shankar Narayanan; Ting-Shan Luk (IEEE Photonics Journal, 2019)
In this paper, we report a direct imaging of narrow-band super Planckian thermal radiation in the far field, emitted from a resonant-cavity/tungsten photonic crystal (cavity/W-PC). A spectroscopic study of the cavity/W-PC shows a distinct resonant peak at λ ∼ 1.7 μm. Furthermore, an infrared CCD camera was used to record radiation image of the cavity/W-PC and a carbon-nanotube (CNT) black reference at λ ∼ 1.7 μm emitted from the same sample. The recorded image displays a higher brightness emitted from the cavity/W-PC region than from the blackbody region for all temperatures tested, T = 530–650 K. This observation is in sharp contrast to the common understanding of equilibrium thermal radiation, namely, a blackbody has a unit absorptance, a unity emittance and should emits the strongest radiation. Since the image was taken from the same sample and the temperature difference across the W-PC/ CNT boundary is less than 0.1 K, the observed image contrast gives a truly convincing evidence of super Planckian behavior in our sample. The discovery of a super-intense, narrow band radiation from a heated W-PC could open up a new door for realizing narrow band infrared emitters. The W-PC filament could also be very useful for efficient energy applications such as thermo-photovoltaics, waste heat recycling and radiative cooling.